DIPLOMASI RUSIA MENGGAGALKAN PERANCANGAN RESOLUSI DEWAN KEAMANAN PBB TENTANG PENEMBAKAN PESAWAT MH-17 MALAYSIA DI DONETSK UKRAINA - Iqbal R.H, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to explain the fall of Malaysia's MH-17 aircraft in the Donetsk region of Eastern Ukriana that killed all passengers on the plane. In this issue the security council issued two resolutions, where the first resolution of resolution 2166 and subsequent resolution failed because Russia exercised its veto as a permanent member.This study uses the public diplomacy theory proposed by Jay Wang, the Neo-Realism perspective, with the level of State analysis. This research also uses descriptive analysis with qualitative approach. Data collection techniques by collecting data data and literature studies.The results of this study indicate Russia's veto is Russia's step to thwart the UN Security Council's Security Council Resolution to raise the matter to the International Court of Justice and Russia has lobbied up to China, Angola and Venezuela.Keywords: shooting, resolution, veto, security council